Unexpected systematic affinities and geographic expansion of a marine alien hydroid (Cnidaria: Hydrozoa). Issue 3 (3rd April 2019) - Song, Xikun; Lyu, Mingxin; Bernhard, Ruthensteiner; Wang, Jianjun; Gravili, Cinzia
Abstract : Biological systematics provides taxonomic information and expertise for biogeography and biological invasion research and management. However, the systematic classification of most taxa, including some alien and invasive species, relies only on morphology. This applies for example to Sertularella tongensis Stechow, 1919 (Cnidaria: Sertulariidae), an alien hydrozoan recently reported in the Mediterranean. Its genus affiliation is still unclear and controversial. Historically, it has been assigned to several existing genera. However, molecular data (COI, 16S, 18S, 28S) provided here do not support these previous assignments. Instead, integrative analyses combining morphological and molecular data support reassigning this species to a new genus, Bicaularia gen. nov. A biogeographic review revealed that this species is widely distributed in the mid- and low-latitude waters of the Indo-Pacific region, and is spreading to some tropical and temperate regions including the Mediterranean and Caribbean Seas, as well as Korea and Japan. This expansion may be attributable to human activity such as shipping through the Suez and the Panama Canals. However, the new record attached to a floating Sargassum algal fragment in the surface water of the open Pacific, might suggest a neglected cryptic spread pathway with the assistance of floating biological organisms. Our findings shed light on the complexity of the phylogeny and spread pathway of the investigated hydrozoan species. We regard the fine systematics as the first step towards future global sampling for molecular studies aiming to elucidate the origins and pathways for alien and invasive species. http://zoobank.org/urn:lsid:zoobank.org : pub: 45AB0849-1E3B-477FB643-1B3B4603C1FF